Analisis Pengaruh Belanja Pemerintah Sektor Kesehatan dan Pendidikan Terhadap Pendapatan Per Kapita di Provinsi Aceh - Nur Aidar; Muhajir Muhajir (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
This study aims to analyses the effect of government expenditure on healht and education sectors on income per capita across districts in Aceh Province. This study used panel data from 2008 to 2011. Random effect model was utilized to calculate error of the model by applying Generalized Least Square (GLS). The results of research indicated that government expenditure on health sector was not statistically significant to income per capita, though they have a positive relation. Meanwhile, education expenditure has statistically a positive impact on per capita income across the districts in Aceh. To accelerate economic development in Aceh, the provincial and districts governments should consider increasing budget allocation to education and health sectors.